2022
DOI: 10.1186/s12870-022-03858-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes of Sorbus sensu stricto (Rosaceae): comparative analyses and phylogenetic relationships

Abstract: Background Sorbus sensu stricto (Sorbus s.s.) is a genus with important economical values because of its beautiful leaves, and flowers and especially the colorful fruits. It belongs to the tribe Maleae of the family Rosaceae, and comprises about 90 species mainly distributed in China. There is on-going dispute about its infrageneric classification and species delimitation as the species are morphologically similar. With the aim of shedding light on the circumscription of taxa within the genus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 88 publications
4
6
0
1
Order By: Relevance
“…Similarly, the IRb/SSC boundary was located within the ycf1 gene, while the IRa/SSC boundary was identified within the duplicated copy of the ycf1 gene. These results are in accordance with previous studies conducted on different species [53,54]. Notably, no major changes in the position of IR regions were observed in the studied plastid genomes, suggesting the absence of substantial structural rearrangements [55,56].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the IRb/SSC boundary was located within the ycf1 gene, while the IRa/SSC boundary was identified within the duplicated copy of the ycf1 gene. These results are in accordance with previous studies conducted on different species [53,54]. Notably, no major changes in the position of IR regions were observed in the studied plastid genomes, suggesting the absence of substantial structural rearrangements [55,56].…”
Section: Discussionsupporting
confidence: 93%
“…The structure, gene orders and GC content were highly conserved and nearly similar in the samples of Sanicula analyzed here, and were also identical to other cp genomes in other genera of Apiaceae and other angiosperms [ 2 , 17 , 20 , 21 , 23 26 ]. The size of the 13 cp genomes varied from 155,335 ( S. flavovirens ; NC_061752 and OP703176) to 155,764 bp ( S. lamelligera ; OP703174) (Table 1 ).…”
Section: Discussionsupporting
confidence: 64%
“…Many works proved that the variation of SSRs in cp genomes were widely used in population genetic studies, species identification and evolutionary relationship [ 26 , 34 , 38 ]. In this study, the characteristics of SSRs and short dispersed repeats (SDRs) were also similar among these Sanicula cp genomes.…”
Section: Discussionmentioning
confidence: 99%
“…is non‐monophyletic in its traditional large circumscription, as evidence in later years has shown that Sorbus s.l. has five main evolutionary branches and is polyphyletic (Lo and Donoghue 2012, Tang et al 2022).…”
Section: Introductionmentioning
confidence: 99%